Pengaruh motivasi dan komitmen terhadap kinerja karyawan - Edi Muhammad Abduh Alhamidi (Amal Insani Foundation, 2023)
The advantages possessed by the company will be able to make the company survive amidst the intense competition in the business world. Companies need human resources who are educated, skilled, and competent in their fields. Company management must pay attention to managing human resources—problems for employee performance at PT. San Fang Indonesia still has a high rate of absenteeism, which creates issues for leaders to motivate employees to carry out work optimally. The method in this study is associative causality which is directed to determine the relationship between two or more variables. The population and sample in this study are employees at PT. San Fang Indonesia, Serang Regency, has as many as 93 people, called a saturated sample. The results showed that simultaneously there is a significant influence of motivation and work commitment on the performance of employees at PT. San Fang Indonesia with a relationship level in the strong category.